Changes in protein profile, ascorbic acid and chlorophyll stability index of wheat (Triticum aestivum L.) seedlings under heat stress and revival conditions - Mahla, Reena; Madan, Shashi; Munjal, Renu; Chawla, Shilpa; Dua, Yogita; Arora, Vinita (Journal of Cereal Research, 2011)
Screening of thirtysix genotypes for thermo-tolerance was done based on wilting of primary leaf and values of chlorophyll fluorescence. Four wheat genotypes, i.e., two tolerant (HW-2045 and WH-1021) and two susceptible (HS277 and WH-147) were selected and polypeptide pattern, levels of ascorbic acid and chlorophyll stability index (CSI) were observed. The observations were recorded in the leaves of control, stressed and revived seedlings on 2nd and 4th day of revival. The least decrease in CSI under high temperature conditions was in tolerant genotype HW-2045 and highest decrease in susceptible genotype WH-147.The higher accumulation of ascorbic acid was observed under heat stress in all the genotypes but level was more in heat susceptible genotypes as compared to heat tolerant genotypes. SDS-PAGE of seedlings under stress conditions revealed the appearance of polypeptide bands of different molecular weight in tolerant and susceptible genotypes, and these polypeptides bands disappeared on revival of 2nd and 4th day. Based on genotypes screening and on polypeptide pattern, out of four genotypes, HW-2045 was found to be the most tolerant and WH-147 as the most susceptible genotype.